A Study on Prosodic Aspects of Kannada Language - N, Rathna; NP, Nataraja; MG, Subrahmanyaiah (Journal of All India Institute of Speech and Hearing)
For the comprehension of speech, not only discrimination of consonants but also cues like stress, inflectional patterns, the melody of the language are necessary. ’The weight given to various perceptual factors in intonation will vary from language to language. For example, users of a tone language attach greater re- lative weight to pitch variations than users of non-tone languages. When we come to rhythm and stress it is clear from observation that languages do differ considerably in the weight given to various factors. It is widely believed that the over-riding factor in stress judgements is the relative loudness of successive syllables but there is little support to this (Fry, 1966).’